Dynamic terminal investment in male burying beetles. (May 2020) - Farchmin, Paige A.; Eggert, Anne-Katrin; Duffield, Kristin R.; Sakaluk, Scott K.
Abstract : The dynamic terminal investment threshold model posits that the propensity of an individual to terminally invest in response to an immediate survival threat, such as an infection, depends on other factors that alter an individual's residual reproductive value. Here, we explore the potential for dynamic terminal investment in burying beetles, insects that inter small vertebrate carcasses as the sole source of food for their offspring and that exhibit extensive biparental care. We injected males at two different ages with heat-killed bacteria and measured their reproductive output, predicting that immune-challenged males would show a longer period of parental care, consume less of the carcass and produce a greater number of larvae in the current reproductive attempt compared with control males. We further predicted that terminal investment would be more evident in older males than in younger ones. Males challenged with heat-killed bacteria as virgins prior to their first reproductive attempt showed no evidence of terminal investment, whereas these same individuals when challenged at a later age as reproductively experienced breeders in a subsequent reproductive attempt showed increased reproductive output. Older, immune-challenged individuals gained less mass during the time on the carcass than control males, suggesting that this terminal investment was subsidized, at least in part, by males refraining from eating as much of the carcass as they might have otherwise done in the absence of an immune challenge, leaving more carrion for their offspring to consume at the expense of their own maintenance and future reproduction. Because it seems likely than an individual's residual reproductive value decreases with both increasing age and reproductive experience, the context-specific terminal investment shown by immune-challenged males in the current study aligns with theory. Highlights: Older male burying beetles terminally invest, but younger males do not. Older immune-challenged males produced more young than control males. Older immune-challenged males consumed less of the carcass than control males. Terminal investment was thus subsidized by older males forgoing feeding. These results align with the dynamic terminal investment threshold model.